Upaya Meningkatkan Motivasi Belajar Seni Rupa Peserta Didik Melalui Media Artsteps dalam Pembelajaran PJBL di Kelas XII IPA 5 SMA Negeri 8 Denpasar - Gusti Ayu Made Puspawati; Putu Dika Pratama; Mirah Rahmawati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The implementation of this research aims to analyze the PjBL learning model by implementing Artsteps media in fostering learning motivation of SMA Negeri 8 Denpasar class XII IPA-5 in the 2023/2024 school year in fine arts subjects. This research is a type of PTK with two cycles, each cycle involving 4 stages of research, namely, (a) planning stage; (b) implementation stage; (c) observation stage; and (d) reflection stage. The subjects in the study were students of SMA Negeri 8 Denpasar class XII IPA-5 which numbered 46 students. Then the methods applied by researchers in collecting research data include literature study, documentation, performance assessment, and observation. The method implemented in data analysis is a quantitative descriptive method, where quantitative methods are implemented to test student performance. Based on the test results that have been carried out in cycle I, the lowest and highest scores in SMA Negeri 8 Denpasar class XII IPA-5 are obtained, namely 60 and 90 with a mean learning outcome of 73. So the success rate of learning outcomes is 72%. Then in cycle II, the lowest and highest scores were obtained at 80 and 95 with a mean learning outcome of 89. Then the learning success rate reached 100%. This indicates that the motivation of students to learn in fine arts subjects has increased as evidenced by the existence of increasingly optimal learning outcomes.